2000
DOI: 10.1136/ewjm.173.3.169-a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a telemedicine program

Abstract: Although referring physicians and patients indicate a high level of satisfaction with telemedicine services and insurers are negotiating reimbursement policies, additional research must investigate the reasons why some payers, patients, and providers resist participation in these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 5 publications
(3 reference statements)
1
20
1
2
Order By: Relevance
“…This study reports less favourable GP responses to telemedicine than observed in previous studies [9][10][11][12][13][14] , and suggests that GPs remain cautious about the introduction of TD into their Practices. It also suggests that using the model of telemedicine described in this paper would not be appropriate and widely acceptable to GPs.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…This study reports less favourable GP responses to telemedicine than observed in previous studies [9][10][11][12][13][14] , and suggests that GPs remain cautious about the introduction of TD into their Practices. It also suggests that using the model of telemedicine described in this paper would not be appropriate and widely acceptable to GPs.…”
Section: Resultscontrasting
confidence: 67%
“…The few studies that do exist suggest high levels of satisfaction among doctors involved in the use of telemedicine. [9][10][11][12][13][14] The authors are aware of no other published studies that have reported upon the views and perceptions of GPs towards asynchronous telemedicine in dermatology over time. Therefore, this paper provides an original contribution to the current telemedicine literature in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic surgery surgical intervention outcomes did not seem to be impacted negatively by the telemedicine and remote management of certain components of the overall care. Patient participation in our telemedicine programs was completely voluntary, and yielded a high satisfaction rate reaffirming experience of other investigators (Nesbitt TS et al, 2000). Also, experience with Fig.…”
Section: Assessing Outcomes and Providing Long-term Care In Plastic Ssupporting
confidence: 81%
“…Telehealth has now been used in the delivery of behavioral treatments, psychological assessments, social skills group treatment, and session evaluations (Alessi, 2002; Cowain, 2001; Deitsch, et al, 2000; Hilty, Sison, Nesbit, & Hales, 2000; Hyler & Gangure, 2003; Monnier et al, 2007). Telehealth has been successfully employed for individuals in rural areas (Brown, 1998; Ermer, 1999; Nesbitt et al, 2000), and for difficult-to-treat patient populations, such as the elderly (Poon et al, 2005), patients with thought disorders (Zarate, Weinstock, Cukor, Morabito, Leahy, Burns, & Baer, 1997), and avoidant/reluctant patients (Brodey, Claypoole, Motto, Arias, & Goss, 2000; Zaylor, Whitten, & Kingsley, 2000). However, to our knowledge, no studies have investigated the delivery of PE via telehealth technology.…”
mentioning
confidence: 99%